Infection of the oral cavity with SARS-CoV-2 variants: Scope of salivary diagnostics - Iyer, Parvati; Chino, Takahiro; Ojcius, David M. (Frontiers in Oral Health, 2022)
Coronaviruses, including SARS-CoV-2, have caused pandemics in the past two decades. The most prevalent SARS-CoV-2 variants of concern are currently the BA.4 and BA.5 subvariants of the Omicron variant, which can re-infect individuals who have been previously infected with other variants or had protection from vaccines targeting the original SARS-CoV-2 variant. There is a high possibility that future antigenic drifts of the SARS-CoV-2 virus will lead to these infections becoming endemic. Given the high risk of transmission of coronavirus via aerosols produced during dental procedures, it is important to understand the future risk of coronavirus infection for oral health professionals and to diagnose quickly early stages of outbreaks. Testing of saliva for coronavirus may be the least invasive and most convenient method for following the outbreak at the individual and community level. This review will describe strategies for diagnosis of coronavirus in saliva..